A Study on Clinical Features of pulmonary Tuberculosis in Pediatric Age Group in Rural Medical College - Kashavoyina Muralidhar; Sarfarz, Mohammad; A Bhaskar (Asian Journal of Clinical Pediatrics and Neonatology, 2021)
Introduction: Tuberculosis is a specific infectious Disease, mycobacteriumTuberculosis which is acid-fast bacilli will cause tuberculosis The disease primarily affects the lungs. It also affects meninges, Intestine, Liver, Joints, Heart, Skin, lymph glands, and called extrapulmonary tuberculosis. Tuberculosis isa very common problem in India and developing countries and African countries. In India 2 million population is affected annually among these 5% patients are in pediatric group 0-16 years. The aim of the study ids to study the prevalence clinical profile of pulmonary tuberculosis in rural medical college. Subjects and Methods: We have examined 140 children, out of these 140, boys were 78 and girls were 62. The age group is between 1year to 16 years. We have conducted this study for 7 months from March 2020 to Nov. 2020, In the department of pediatrics in association with the department of pulmonology in kaminani medical college. Results:We have included 140 Childrens in this study boys were 78 and girls were 62. The Commonage group is between 10 yrs -16yrs. Bilateral. Lesions were noted in 25 cases. The lesions noted are infiltration, fibro cavitary lesions, and consolidation and pleural effusion, and empyema. Conclusion:Pulmonary tuberculosis is a very common infectious disease in India, especially in rural areas, the younger age group is more commonly involved. Still, mortality is high in the rural part of India. Study design: It is an analytical study conducted in rural area to know the prevalance and the pattern of clinical features of pulmonary tuberculosis in children who are residing in different areas with different socio-economic back groud. In our area the population density is not high. It is a cluster of small village. Where proper medical facilities are not available prevalance in India is 10% - 22%, In our area the prevalance is 26% -28%.